2015
DOI: 10.1177/1077558715589705
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Doctors’ Working Hours

Abstract: The study examined changes in doctors' working hours and satisfaction with working hours over five time points and explored the influence of personal characteristics on these outcomes. Latent growth curve modeling was applied to Medicine in Australia: Balancing Employment and Life data, collected from 2008 to 2012. Findings showed that working hours significantly declined over time, with a greater decrease among males, older doctors, and doctors with fewer children. Satisfaction increased faster over time amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…Such gendered working patterns are important considerations for medical workforce planners, particularly given women’s increasing representation in the medical workforce [ 2 ]. Recent studies, however, have shown that doctors of both sexes are working fewer hours than in the past [ 4 6 ], with male doctors showing the greater rate of decline in working hours [ 7 , 8 ]. In the UK, requests to enter LTFT training have increased, facilitated by recent legislation granting all employees the right to request flexible and LTFT working hours (not just parents) [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such gendered working patterns are important considerations for medical workforce planners, particularly given women’s increasing representation in the medical workforce [ 2 ]. Recent studies, however, have shown that doctors of both sexes are working fewer hours than in the past [ 4 6 ], with male doctors showing the greater rate of decline in working hours [ 7 , 8 ]. In the UK, requests to enter LTFT training have increased, facilitated by recent legislation granting all employees the right to request flexible and LTFT working hours (not just parents) [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, requests to enter LTFT training have increased, facilitated by recent legislation granting all employees the right to request flexible and LTFT working hours (not just parents) [ 4 , 9 ]. Authors of some studies have indicated that this move to reduced working hours for doctors represents a cultural shift in valuing time over money and prioritising work-life balance above career progression [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our scenario, which assumed an increase in the number of male GPs working in urban areas moving to part-time work based on research by Joyce et al [34, 35], reduced the surplus and resulted in a balanced workforce by 2033. While this was a non-policy scenario, incentives to move GPs to part-time work could be investigated to reduce existing surpluses.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore instrument hours worked with a set of indicators capturing GP family type. Family circumstances, such as having young dependent children and the working status of the spouse, have been shown in previous studies to be strongly correlated with hours worked (Becker, 1985;Bertrand & Hallock, 2001;Joyce, Wang, & Cheng, 2015;Schurer et al, 2016). For these family characteristics to be valid instruments, in addition to being correlated with the GP's hours worked, they should not impact on the demand for GP consultations and hence waiting times through any mechanism other than the hours worked by GPs.…”
Section: Econometric Strategymentioning
confidence: 92%